ANALISIS DEFLEKSI AKIBAT BEBAN ANGIN PADA BEJANA TEKAN VERTIKAL DI KELURAHAN SAGERAT KOTA BITUNG - Farrell S Kiling; Stenly Tangkuman; Hengky Luntungan (JURNAL POROS TEKNIK MESIN UNSRAT, 2016)
Nowdays, the industry plays a vital role in the economy; therefore design of an efficient plant industry is very important. There is a component for handling a pressurized fluid, such as a pressure vessel. The purpose of this study was to determine the maximum deflection occurs at a vertical pressure vessel due to wind loads, and obtains maximum height of pressure vessels based on the allowable deflection. The object of this research is in Bitung. Bitung is one of the industrial cities located in the Province of North Sulawesi. Wind velocity was obtained from BMKG Bitung Maritime Station. Analysis of deflection applied to pressure vessel which has height of 25 ft to 150 ft. The results showed that the higher the pressure vessel, the higher the deflection. The maximum deflections for height of 25 ft to 150 ft have been determined. Furthermore, based on allowable deflection, the allowable height of the pressure vessel in Sagerat Village-Bitung City is 147.44 ft. Keywords         : Wind Load, Pressure Vessel, Deflection, Bitung